SOLVATION STRUCTURE DETERMINATION OF Ni2+ ION IN WATER BY MEANS OF MONTE CARLO METHOD - Tutik Arindah; Bambang Setiaji; Harno Dwi Pranowo (Universitas Gadjah Mada, 2002)
Determination of solvation structure of Ni2+ ion in water has been achieved using Monte Carlo method using canonic assemble (NVT constant). Simulation of a Ni2+ ion in 215 H2O molecules has been done under NVT condition (298.15 K). The results showed that number of H2O molecules surround Ni2+ ion were 8 molecules in first shell and 17 molecules in second shell, interaction energy of Ni2+-H2O in first shell was -68.7 kcal/mol and in second shell was -9.8 kcal/mol, and there were two angles of O-Ni2+-O, i.e. 74o and 142o. According to those results, the solvation structure of Ni2+ ion in water was cubic antisymetric.